PERAN BANK SYARI’AH DALAM MEMBANTU BERKEMBANGNYA KEWIRAUSAHAAN DI INDONESIA - Satyawidya, Patricia (Jurnal Akuntansi AKUNESA, 2013)
A country that wants to be a developed country should have a lot of entrepreneurs. Because entrepreneurs can create jobs and increase state revenues. To create and realize the country has a lot of entrepreneurs who needed an agency that can provide financing assistance fund business investment. Surely these funds to be really fit and well worth the debtor owned condition. Sharia banks should contribute to provide easiness of financing that entrepreneurs obtain the capital resources that really suit the situation. Sharia banking conditions in the future to facilitate the business world will be a lot depends on the ability of sharia banks in presenting interesting products, competitive, according to the needs of entrepreneurs, but still in accordance with the principles of Sharia, because the Sharia banking should be more creative and innovative in designing products and services. Keywords: Syari?ah Banking, The business world, Enterpreneur